Knowledge and Practices of Retail Drug Sellers on the Rational Dispensing of Antibiotics - Akash, Md Mahir Faisal; Sultana, Hafiza; Islam, Md Ziaul; Rayhan, Md Golam; Ferdouse, Mashruba; Mohammad , Nurunnabi (Journal of Monno Medical College, 2025)
Background: Retail drug pharmacies are often the primary and sometimes the sole source of healthcare for many patients in developing countries. The nonprescription selling of antibiotics is a major contributor to the rise in antibiotic usage, hastening the emergence of drug resistance. Bangladesh, as a developing country with a growing economy, is currently facing the global health threat of antibiotic resistance. Objective: The purpose of the present study was to assess the levels of knowledge and practices of retail drug sellers regarding the rational dispensing of antibiotics. Methodology: This cross-sectional study was conducted from January to December 2018 to evaluate the levels of knowledge and practices among the conveniently selected 294 retail drug sellers regarding the rational dispensing of antibiotics. Pharmacies were purposively selected from the Fatulla and Narayanganj Sadar Narayanganj districts of Dhaka, Bangladesh. Results: Most retail drug sellers had an average level of practice (68.3%), in contrast to the majority had good knowledge level (94.5%). Compared to older dealers (aged 41-60); younger sellers (aged 21-40) were significantly more likely to prescribe antibiotics without a prescription. On the contrary, retail drug sellers with a higher daily client volume were significantly more likely to dispense antibiotics without a prescription than those with fewer clients. Conclusion: This study revealed that while most retail drug sellers had a good level of knowledge, the majority demonstrated only an average level of practice. Journal of Monno Medical College December, 2024;10 (2):61-67